2017
DOI: 10.1186/s12879-017-2590-7
|View full text |Cite
|
Sign up to set email alerts
|

Spread of resistant gram negatives in a Sri Lankan intensive care unit

Abstract: BackgroundInfections with multi drug resistant (MDR) organisms are a major problem in intensive care units (ICUs). Proper infection control procedures are mandatory to combat the spread of resistant organisms within ICUs. Well stablished surveillance programmes will enhance the adherence of the staff to infection control protocols. The study was conducted to assess the feasibility of using basic molecular typing methods and routine hospital data for laboratory surveillance of resistance organisms in resource l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…These observations may at least partly be associated with the frequent usage of carbapenems and ventilator equipment in ICU settings. Similarly, high rate of respiratory CRE (38.1%; 2/7 E.coli and 6/14 K. pneumoniae) has been reported in the ICUs of a tertiary care hospital in the Central Province of Sri Lanka ( 30). Additionally, in the present study, an alarmingly high prevalence of CRE (83.3%) was found among the blood culture Enterobacteriaceae isolates of ICU origin.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These observations may at least partly be associated with the frequent usage of carbapenems and ventilator equipment in ICU settings. Similarly, high rate of respiratory CRE (38.1%; 2/7 E.coli and 6/14 K. pneumoniae) has been reported in the ICUs of a tertiary care hospital in the Central Province of Sri Lanka ( 30). Additionally, in the present study, an alarmingly high prevalence of CRE (83.3%) was found among the blood culture Enterobacteriaceae isolates of ICU origin.…”
Section: Discussionsupporting
confidence: 74%
“…Intensive care units (ICUs) are known reservoirs for multi-drug resistant bacteria in healthcare settings due to the presence of high antibiotic pressure and higher propensity for cross-contamination ( 30,31). Considering the antibiotic resistance in the cohort of Enterobacteriaceae isolated from the clinical samples of the ICUs, we found that high overall prevalence of CRE (38.7%; 12/31), which was significantly higher than the prevalence of ESBL-PE (22.6%; 7/31) detected in the same group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it should be kept in mind that the studies reported here assessed a non-outbreak situation in western countries. A study assessing the ESBL-E respiratory colonization in Sri Lanka suggested a higher cross-transmission rate but no data are provided about the imported or acquired status of ESBL-E colonization [48]. Further studies are needed to assess the rate of cross-transmission and the efficacy of hygiene procedures in non-western countries which have a higher prevalence of ESBL-E [2, 16].…”
Section: Discussionmentioning
confidence: 99%
“…In the past 20 years, there has been a pronounced increase in the emergence of multiple resistance of Gram-negative bacterial infections, especially multiresistant Klebsiella pneumoniae, Acinetobacter baumannii and Pseudomonas aeruginosa (Lachiewicz et al, 2017;Tissera et al, 2017). Due to the slow developmental process of new antibiotics, colistin has been considered as the last-line therapy for the treatment of multiresistant Gram-negative bacterial infections (Li et al, 2006).…”
Section: Introductionmentioning
confidence: 99%